The Impact of Gender Diversity and the Global Financial Crisis on Firm Performance Through ESG Dimensions - Darmayani, Ni Luh Manik; Asri Dwija Putri, I Gusti Ayu Made (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study investigates the impact of gender diversity in corporate leadership and the global financial crisis on the performance of banking companies in Southeast Asia, considering the role of environmental, social, and governance practices as a mediating factor. Driven by the increasing emphasis on inclusive governance and sustainable strategies, this research aims to understand how leadership composition and external economic pressures jointly shape organizational outcomes. The analysis focuses on publicly listed banks across Indonesia, Malaysia, the Philippines, Singapore, and Thailand from 2018 to 2023. Using a quantitative approach with panel data regression, data were compiled from board composition databases, financial indices reflecting economic stability, and environmental, social, and governance scores. The results reveal that gender diversity has a negative direct influence on firm performance, while the economic downturn due to the global financial crisis significantly reduces company value. In contrast, strong environmental, social, and governance practices enhance firm performance and play a critical mediating role by channeling the effects of board diversity and financial conditions into overall outcomes. These findings underscore the importance of cultivating not only diverse leadership but also robust sustainability frameworks to strengthen resilience and long-term value in the banking sector.